2009
DOI: 10.1002/ejoc.200900911
|View full text |Cite
|
Sign up to set email alerts
|

Supported Chiral Monodentate Ligands in Rhodium‐Catalysed Asymmetric Hydrogenation and Palladium‐Catalysed Asymmetric Allylic Alkylation

Abstract: A family of monodentate polystyrene-supported phosphites, phosphoramidites and phosphanes has been prepared and evaluated as ligands in rhodium-catalysed asymmetric hydrogenation and palladium-catalysed asymmetric allylic alkylation. The supported ligands yielded active and enantioselective catalysts, which in selected cases match the performance of the nonsupported counterparts. As expected, the performance of the supported ligands in the rhodium-catalysed hydrogenation depends on the nature of the ligand, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…Kamer and co-workers obtained their best result with L134, with an ee of 58% in AAA (Fig. 45) [160]. ZhiDong and co-workers had a better ee of 64% in AAA with their ligand L135, using N-methyaminomethyl polystyrene resin [161].…”
Section: Polymer Supported Ligandsmentioning
confidence: 95%
“…Kamer and co-workers obtained their best result with L134, with an ee of 58% in AAA (Fig. 45) [160]. ZhiDong and co-workers had a better ee of 64% in AAA with their ligand L135, using N-methyaminomethyl polystyrene resin [161].…”
Section: Polymer Supported Ligandsmentioning
confidence: 95%
“…Kamer and co-workers supported several monodentate phosphorus ligands by reaction of hydroxylsubstituted polystyrene with phosphorus chlorides in the presence of a tertiary amine as base ( Figure 10). [123] The polymeric ligands were tested in the Rh-catalyzed asymmetric hydrogenation and Pdcatalyzed alkylation. Interestingly in comparison to non-supported parent ligands in several instances inferior enantioselectivities yielded, which confirm earlier observations by Doherty et al [124] However, a general correlation between supported and non-supported catalysts was not found.…”
Section: Supramolecular Ligandsmentioning
confidence: 99%
“…Kamer and co-workers investigated the use of polymer-bound phosphoramidites, phosphites and related ligands in the asymmetric substitution of an allylic acetate using dimethylmalonate as the nucleophile, but found that although the conversion was high, the enantioselectivity was rather modest and not at the same level as seen for the solution phase counterparts [ 38 ]. Better results were obtained by Vidal-Ferran, Pericàs and colleagues who applied polymer bound diphenylphosphinooxazoline (PHOX) ligands in enantioselective amination of allylic acetates [ 39 ].…”
Section: Palladiummentioning
confidence: 99%